GhMYB44 enhances stomatal closure to confer drought stress tolerance in cotton and Arabidopsis - Duan, Bailin (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.